2013
DOI: 10.32473/edis-in1004-2013
|View full text |Cite
|
Sign up to set email alerts
|

Natural Enemies of Rugose Spiraling Whitefly, Aleurodicus rugioperculatus Martin (Insecta: Hemiptera: Aleyrodidae) in the South Florida Landscape

Abstract: Rugose spiraling whitefly was first observed in south Florida in 2009. It has been found in 17 counties in south and central Florida. This whitefly has been reported on more than 60 plant species, which include gumbo limbo, coconut, black olive, avocado, Calophyllum spp., and giant white bird of paradise. This 6-page fact sheet describes the predators and parasitoids found feeding on this whitefly in the south Florida landscape. Written by Siavash Taravati, Catharine Mannion and Holly Glenn, and published by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 3 publications
2
2
0
Order By: Relevance
“…Natural Enemies: Encarsia guadeloupae Viggiani (Hymenoptera: Aphelinidae), a well known parasitoid of A. dispersus (Ramani et al 2002;Evans, 2007), was found to parasitise A. rugioperculatus. This has already been reported on A. rugioperculatus from Florida (Kumar et al, 2013;Taravati et al, 2013) and appears to be a potential biocontrol agent against RSW as 50 to 60% natural parasitisation of the pupae was observed (Figs. 7, 8A to 8G).…”
Section: Host Plants Ofsupporting
confidence: 74%
“…Natural Enemies: Encarsia guadeloupae Viggiani (Hymenoptera: Aphelinidae), a well known parasitoid of A. dispersus (Ramani et al 2002;Evans, 2007), was found to parasitise A. rugioperculatus. This has already been reported on A. rugioperculatus from Florida (Kumar et al, 2013;Taravati et al, 2013) and appears to be a potential biocontrol agent against RSW as 50 to 60% natural parasitisation of the pupae was observed (Figs. 7, 8A to 8G).…”
Section: Host Plants Ofsupporting
confidence: 74%
“…Consequently, the efficacy of synthetic chemical insecticides in such a case demands further investigation. These findings are also supported by Taravati et al (2013). Many reported plant species are expected to be incidental hosts that cannot sustain long-term rugose spiraling whitefly populations and, therefore, need minimal or no management practices.…”
Section: Control Of Rugose Spiraling Whiteflysupporting
confidence: 64%
“…Juss., Manihot Out of the nine natural enemy fauna collected from the RSW infested palms (Table 4), eight were predators of the family Coccinellidae (6) and Chrysopidae (2) and one was the aphelinid parasitoid, Encarsia guadeloupae Viggiani. Though a rich and diverse predatory fauna was observed on the infested palms, the natural parasitism by E. guadeloupae ranged from 4.5 to 78.2 per cent (Table 5), indicating the essential role of the aphelinid parasitoids in infested gardens (Taravati et al, 2013). Though the coccinellid, Nephaspis oculata was reported to be an effective predator of RSW in Florida (Francis et al, 2016), this species could not be recovered in the present investigations.…”
Section: Plate 1 Distinguishing Features For the Identification Of A ...mentioning
confidence: 58%